Eustress: A Key to Improving Job Satisfaction and Health among Thai Managers Comparing US, Japanese, and Thai Companies Using SEM Analysis - Jarinto, Krit (NIDA Development Journal, 2012)
Eustress or positive stress is defined as stress which enables employees to perform better and increase their job satisfaction. This study confirms that eustress is a key factor in motivating employees to achieve high performance and enhanced job satisfaction. Not enough eustress lead to employee boredom and turnover. On the other hand, large amount of negative stress or distress significantly leads to physical and psychological illness. Exclusive stimulation or too much negative stress is likely to cause illness. Both quantitative and qualitative data were collected for this research. Structural equation modeling techniques were used for statistical data analysis together with in-depth interview analysis of Thai managers reporting to US, Japanese, and Thai senior managements. ความเครียดด้านบวกเป็นสิ่งที่กระตุ้นให้พนักงานภายในองค์กรสามารถปฏิบัติงานได้ดีขึ้นและมีความพึงพอใจในงานของตน. จากการศึกษานี้สามารถยืนยันได้ว่าพนักงานควรมีความเครียดในระดับที่เหมาะสมจึงจะทำให้พนักงานมีแรงจูงใจในการทำงานมากขึ้น ซึ่งเป็นปัจจัยสำคัญในการที่จะทำให้พนักงานมีความท้าทายในงานที่ตนเองรับผิดชอบและส่งผลทำให้อัตราการลาออกลดลง. ถึงอย่างไรก็ตามการที่ผู้จัดการสร้างแรงกดดันในการทำงานมากจนเกินไปจะส่งผลทำให้พนักงานเจ็บป่วยทั้งทางด้านร่างกายและจิตใจ. การศึกษาครั้งนี้เป็นการศึกษาโดยใช้เชิงปริมาณและเชิงคุณภาพ การวิเคราะห์โมเดลสมการโครงสร้างพร้อมกับการสัมภาษณ์เชิงลึกเพื่อเป็นการยืนยันผลกับผู้จัดการ คนไทยที่ปฏิบัติงานอยู่ในองค์การที่เป็นของอเมริกา ญี่ปุ่น และไทย